A determination of ecotourism intentions towards the sustainable environment for the future of tourism - Ismail, Fadillah; Imran, Amina; Chew, Boon Cheong; Khan, Nohman; Qureshi, Muhammad Imran (PKP, 2020)
Environmental conservation is one of the very important phenomena in recent times, that is works to conserve the natural environment and deliver to the economy. In recent years, researchers show interest in behavioral intentions for the sustainable development of natural areas. In this study, we find literature published during the years 2009 to 2018 on the very rising topic of ecotourism intention. For that Scopus database is selected to find out the number of studies published on ecotourism intention. The PRISMA statement templet is used to explain the overall process of selection and rejections of Article for the review of Ecotourism intentions. The final 52 articles with a minimum of 10 citations for the review are selected to analyze the literature to find the gap and direction of ecotourism. Year base, journal base, subject base, and a minimum of 10 citations are done in the methodology part. Finally, the classification of data is done as per results from the quality assessment process. behavioral intentions and environmental sustainability are discussed widely by the researchers and theoretical preferences are the theory of planned behavior is used in maximum studies. The findings of the study showed that ecotourism intentions are strongly affected by the education, conservation of natural resources that are converted into behaviour.